Dreams and disappointments regarding nursing: Student nurses' reasons for attrition and retention. A qualitative study design. (July 2017) - ten Hoeve, Yvonne; Castelein, Stynke; Jansen, Gerard; Roodbol, Petrie
Abstract: Background: In the Netherlands, hundreds of students register annually for a nursing programme, but not all of these students manage to complete their training. Objective: The main aim of this study was to examine which factors affect student nurses' decision to leave or complete their programme. Theoretical framework: The study used an exploratory descriptive design, employing a qualitative phenomenological approach. Sample: Student nurses ( n = 17) at the beginning of their third year of the four-year Bachelor's programme. Data collection: Data were collected at four Universities of Applied Sciences in the Netherlands, from December 2013 to January 2014. Semi-structured interviews were used to collect the data, using an interview guide. Results: The main reasons for students to become nurses were the caring aspect, personal experiences with healthcare, role models in their immediate environment, and job opportunities. They had both altruistic and professional perceptions of their profession. Reasons for attrition were strongly related to the training programme and to their clinical placements, in particular the perceived lack of support from mentors and team. Feelings of being welcomed and working in a nice team proved to be more important reasons for completing the programme than the specific clinical field. Conclusions: Student nurses started their studies with many dreams, such as caring for people and having the opportunity to deliver excellent nursing care. When their expectations were not met, their dreams became disappointments which caused them to consider stopping and even to leave (attrition). The role of lecturers and mentors seems invaluable in protecting and guiding students through their programme and placements. Optimal cooperation between lecturers and mentors is of paramount importance to retain student nurses in their training programmes. Highlights: Student nurses start their education with many dreams, such as caring for people. During the first two years of training many dreams became disappointments. Teaching staff and clinical placements were related to attrition and retention. Being welcomed in a team had more influence on retention than the clinical field.